Innovative Thinking and its Representations in Interior Space Design: علاء الدين كاظم منصور الإمام (Al-Academy, 2020)
The current research studies the innovative thinking system in the field of the interior design, and the extent of the possibility of activating its work mechanisms as a strategy for the redesigning principle according the variables of the contemporary social thinking. The research aims at revealing the nature of the thinking criteria and requirements that provide strategic values that guide the interior designer and the architect to organize the mechanism the act of designing. It also contributes in dealing with the design product through activating its ability in innovation and redesigning. The research consists of the concept of innovation, the qualitative levels and the basic classifications, in addition to dealing with the most important criteria and requirements for activating the creative side of the designer and the objectives envisioned by it which call for the continuation of the possibility and redesigning the innovated from in a way that secures the closeness from the aesthetic and functional integration of the design form and it gives the recipient a sense of pleasure and acceptance.The research also deals with the redesign principle as a binding condition for the process of innovation. The most important contemporary technologies that called the designers to work according the mentioned principle. The research reached at a number of conclusions including:The ultimate goal is manifested in activating the redesign principle through developing and advancing the concepts, attitudes, knowledge, skills, the functional and organizational structures, and systems and styles of design, in addition to creating the suitable organizational atmosphere for innovation and positive interaction between the human being and the environment.